Does corporate governance affect the performance of Islamic banks? new insight into Islamic countries - Aslam, Ejaz; Haron, Razali (Emerald Insight, 2020)
Purpose – Corporate governance plays a significant role to overcome agency issues and develop the culture of transparency and openness. In this context, this paper aims to examine how corporate governance mechanisms affect the performance of Islamic banks (IBs). Design/methodology/approach – Stepwise, two-step system generalize method of moment estimation technique is used in the analysis in which control variables are added into the model sequentially. This study used data on 129 IBs from 29 Islamic countries (Middle East, South Asia and Southeast Asia) during the period of 2008 to 2017. Findings – The findings suggest that the audit committee (AUDC) and Shariah board (SB) have positive impact on the performance of IBs (return on assets and return on equity). However, board size and risk management committee have negative and significant effect on the performance of IBs. CEO duality and non-executive directors have mixed relationship with the performance of IBs. These results support the argument that IBs need to improve their financial performance through appropriate governance mechanism. Research limitations/implications – The findings of the study added a new dimension to the governance research that could be a valuable source of knowledge for policymakers and regulators to improve the existing governance mechanismfor better performance of IBs. Originality/value – The study fills the gap in the literature by addressing the issue of corporate governance on performance of IBs across countries. Agency theory is discussed to explain the relationship between corporate governance mechanismand performance. Keywords Financial performance, Corporate governance, Islamic banks, Shariah board, 2SYS-GMM Paper type Research paper